2017
DOI: 10.2741/e792
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cardiac allograft vasculopathy Challenges and opportunities

Abstract: Cardiac allograft vasculopathy (CAV) is one of the most common long-term complications in patients following heart transplantation. Because of its irreversible nature, early detection is essential to impact progression. Thus, imaging techniques play a crucial role in the diagnosis and subsequent treatment. Major advancements in imaging and analysis are required to overcome the limitations of current techniques. Coronary angiography which is the standard method, presents low sensitivity in detection, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
(129 reference statements)
0
0
0
Order By: Relevance
“…SPECT is a nuclear imaging method utilizing gamma-ray emissions. Several research studies have provided a range of sensitivity values (from 21% to 92%) and specificity values (from 55% to 100%) for CAV diagnosis [98]. Recent studies have generally shown improved diagnostic accuracy [99,100].…”
Section: Cardiac Computed Tomography Angiography and Nuclear Imagingmentioning
confidence: 99%
“…SPECT is a nuclear imaging method utilizing gamma-ray emissions. Several research studies have provided a range of sensitivity values (from 21% to 92%) and specificity values (from 55% to 100%) for CAV diagnosis [98]. Recent studies have generally shown improved diagnostic accuracy [99,100].…”
Section: Cardiac Computed Tomography Angiography and Nuclear Imagingmentioning
confidence: 99%